(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Phyllanthus amarus Schumach. & Thonn. is an annual plant distributed throughout India. In Ayurvedic classics, it is identified under the names Bhumyamalaki or Tamalaki and stands out as a significant therapeutic agent in Ayurvedic medicines. Pharmacognostic studies are important for identification and for determining the quality and purity of crude drugs. The aim of the study was to evaluate the preliminary pharmacognostic characters of Phyllanthus amarus Schumach. & Thonn. The pharmacognostic evaluation included a thorough examination of the macroscopic, microscopic, and physicochemical characteristics. The assessed parameters comprised foreign matter, moisture content, total ash, acid-insoluble ash, water-soluble extractive, alcohol-soluble extractive, fibre content and sugar contents, qualitative chemical analysis and High-Performance Thin Layer Chromatography. Macroscopic study showed a taproot system with a straight, cylindrical, light brown root and abundant secondary and tertiary rootlets. The stem was slender, glabrous, exhibiting a smooth and green surface. The leaves were simple, elliptic-oblong in shape with entire margin, arranged alternately. The microscopic examination of the root revealed starch grains and crystals present notably in both the cortex and phloem regions. The stem exhibited Calcium oxalate crystals in the pith region. Numerous anisocytic stomata were observed in the lower epidermis of leaf with stomatal index 25.18%. The water-soluble extractive was found to be more than alcohol soluble extractive. Total sugar was found to be 5.6%. HPTLC at 575nm showed 9 peaks with Rf value ranging from 0.04 to 0.9. With these research findings, it becomes possible to establish pharmacognostic standards for the plant. This, in turn, simplifies the process of identifying and ensuring the purity and quality of Phyllanthus amarus Schumach. & Thonn.